Facile, alternative synthesis of spherical-like ca(H2PO4)2•H2O nanoparticle by aqueous-methanol media - Kongteweelert, Samart; Ruttanapun, Chesta; Thongkam, Montree; Chaiyasith, Pachernchaipat; Woramongkonchai, Somsak; Boonchom, And Banjong (My University, 2013)
Spherical-like calcium dihydrogenphosphate monohydrate (Ca(H2PO4)2•H2O) nanostructure was successfully prepared by the mixing of calcium carbonate and phosphoric in aqueous-methanol media at ambient temperature for 30 min. Three thermal decomposition step and higher stability at over 800°C of the prepared sample are different from the earlier works. Spherical-like Ca(H2PO4)2•H2O nanostructure with diameter < 100 nm confirmed by SEM may be important for potential applications. This method of synthesis by aqueous-methanol media is a fast and simple method and it is expected to be applicable for the synthesis of other nanocrystalline calcium phosphates. © (2013) Trans Tech Publications, Switzerland.
Keywords: Aqueous-methanol media; Calcium phosphate; Characterization; Spherical-like nanostructure